An empirical analysis of an alternative model of Financial Accounting Standard no. 128: Earnings per share. Issue 4 (5th November 2018) - McEnroe, John E.; Sullivan, Mark
Abstract : Purpose: This paper aims to investigate the empirical effects of an inconsistency in the calculation of the diluted earnings per share (EPS) number which originated in Accounting Principles Board Opinion No. 15 (APB 15) and continues in Statement of Financial Accounting Standard No. 128 (SFAS 128), EPS. The discrepancy involves the treatment of dilutive warrants and options versus other dilutive convertible securities and is explained in the section of this paper where the authors describe the proposed alternative EPS model. In a sample of 55 publicly traded companies in which they applied their model, it was found that the average increase in diluted EPS to be 5.7 per cent and the median increase to be 3.8 per cent. The authors believe that SFAS 128 should be considered, along with other factors, to be revised to direct that diluted EPS be computed in accordance with their model. Design/methodology/approach: The authors selected a sample of companies from the Compustat Annual Database that had either Convertible Debt or Convertible Stock or both with a year-end between July 1, 2011 and July 1, 2012 which was the most recent data available at the time of the initial study. They then used the model assuming a "repurchase" of common shares as if the "treasury stock method" which applies to options and warrants also applied to these conversions. They then reduced the number of shares initially used to compute diluted EPS by the number of assumed repurchased shares. Using the revised number of shares, the authors recomputed diluted EPS as a percentage of the originally reported diluted EPS. Findings: For the 55 companies in the sample, the average increase in diluted EPS using the "treasury stock method" was 5.7 per cent. The median increase was 3.8 per cent. The largest increase was 26.6 per cent and the smallest was 0 per cent. Research limitations/implications: This is a one-year study of the sampled firms. A multi-year sample is recommended for further research. Also, the sample might be applied to foreign entities under the jurisdiction of IAS 33. Practical implications: According to the Financial Accounting Standards Board (FASB) the price-earnings ratio of an equity is perhaps the most frequently cited statistic in the business of equity investments. As the denominator in the price-earnings ration is the "diluted" EPS figure calculated under generally accepted accounting principles (GAAP) under Statement of Financial Accounting No. 128 (SFAS 128), the results have very significant implications for the recommended study and revision of the diluted EPS statistic. Social implications: If the current diluted EPS reported numbers result in lower stock prices than would otherwise be the case under the authors' model, then it seems likely that these companies with large amounts of debt would have a higher cost of equity capital than would otherwise be the case. The overall result would be a different allocation of equity capital than would be the case if convertible debt and convertible equity were treated the same way as options and warrants. As we are unaware of a rationale for the disparate treatment, it is believed that this a is a misallocation caused by a statement of the Financial Accounting Standards Board (FASB) that seems flawed and recommend that it be considered to be revised. Originality/value: A review of the literature found no other study addressing this issue.